Devido processo legal substancial e a função administrativa - Birello, Guilherme Tadeu Pontes (2014)
The present study had as its scope, the delimitation of the legal concept of the Due Process of Law clause, in its substantial sense and its implication in the exercise of the administrative function. The mentioned clause is one of the oldest and intrinsic institutes of the Rule of Law. In its incipient form, the Due Process of Law clause represented one of the first methods to control the despotic power. Thenceforth, it was the skeleton for the rise of many others institutes that limits the State Power. From the formal procedural aspect procedural instruments (full defense and the right to appeal, motivation of the State decisions duty, among others), up to reaching the merits of the decision control (originally accepted as reasonableness judgment), this last one known as Substantial Due Process of Law. Occurs that this range of principles typically assigned to the Substantial Due Process of Law clause (reasonableness, proportionality, motivation) has express and specific legal provision in the normative text, demonstrating an emptying of its content in the Brazilian legal order. Nevertheless, it‟s a duty for the legal scholar to apply sense and unity to the judicial system. Within the national legal system, the mentioned principle reveals itself as a command to the law enforcer to seek the best ruling. The best ruling is the one, firstly, that promotes the public interest duty (therefore, preceded by a direct judgment of the will of the normative command and not by an arbitrary subjective judgment) and, in front of the actual reality, has been shown as the most effective. As issued by a competent authority, the decision will be considered, a priori, as the best decision, except if proved that other decision is sufficiently more favorable. It was noted that this assertion has harmony with the administrative role and the legal administrative regime. The exercise of the administrative role is, before anything, the common good promotion, the public interest. This implies in the assertion that the exercise of the prerogatives (Power) given to the administration are instrumentals and, therefore, may only be exercised for the achievement of the public interest set forth in its own judicial order (full submission to the principle of legality). Thereby, it is not granted to the legal scholar any freedom of action, as a public agent, in seek for another purpose but the public interest. Thus, the administration role is to always seek for the best solution for the concrete cases that are presented. Throughout the General Theory of Law elements description, it was sought to present means and procedures in order to seek the best decision (worth mentioning, hermeneutical notions of principles that provide an unitary and systemic comprehension of the judicial order, ratio of principles and rules, weighing judgment and enforcement of the proportionality and reasonableness principles